Review of 1971/05/28 Concert at Barber Institute of Fine Arts (University of Birmingham) Lunchtime Concert of works of the late 19th and 20th Centuries given by members of the Osiris Music Group. - Potter, Keith (Contact: A Journal for Contemporary Music (1971-1990), 1971)